1987
DOI: 10.1073/pnas.84.19.6854
|View full text |Cite
|
Sign up to set email alerts
|

Effective tumor immunotherapy directed against an oncogene-encoded product using a vaccinia virus vector.

Abstract: We have constructed a vaccinia virus recombinant that expresses the extracellular domain of the rat neu oncogene-encoded protein, a 185-kDa transmembrane glycoprotein termed p185. Strain NFS mice immunized with this recombinant virus developed a strong antibody response against the neu oncogene product and were fully protected against subsequent tumor challenge with neu-transformed NIH 3T3 cells. No tumor immunoprotection was found when recombinant virus-immunized mice were challenged with Ha-rastransformed NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…Full -length, rather than extracellular domain, GA733 Ag was used for these studies to detect potential activation of T lymphocytes by intracellular epitopes present in the VV GA733 -2 vaccine. 51 Cr release (see below ) of the labeled cells. Lysis of target cells by mouse lymphocytes was determined in vitro using a standard 51 Cr-release assay.…”
Section: Antibody -Dependent Cell -Mediated Cytotoxicity ( Adcc ) Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Full -length, rather than extracellular domain, GA733 Ag was used for these studies to detect potential activation of T lymphocytes by intracellular epitopes present in the VV GA733 -2 vaccine. 51 Cr release (see below ) of the labeled cells. Lysis of target cells by mouse lymphocytes was determined in vitro using a standard 51 Cr-release assay.…”
Section: Antibody -Dependent Cell -Mediated Cytotoxicity ( Adcc ) Assaysmentioning
confidence: 99%
“…51 Cr release (see below ) of the labeled cells. Lysis of target cells by mouse lymphocytes was determined in vitro using a standard 51 Cr-release assay.…”
Section: Antibody -Dependent Cell -Mediated Cytotoxicity ( Adcc ) Assaysmentioning
confidence: 99%
“…In addition, immunization with a vaccinia virus expressing the extracellular domain of ErbB-2 induced both cellular and humoral immune responses against ErbB-2 that protected against subsequent tumor challenge. 27 Recently, we have shown dendritic cells infected with AderbB-2⌬tk could induce protective immunity against NDL tumor cell challenge and dramatically suppressed the growth of pre-existing tumors. 28 Enhanced AderbB-2⌬tk antitumor efficacy was observed in immune-competent FVB mice as compared with immune-deficient SCID Beige mice (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immunization of mice with a vaccinia virus expressing the extracellular domain of ErbB-2 induced immune responses against ErbB-2 that protected against subsequent tumor challenge. 27 Recently, we have demonstrated that dendritic cells transduced ex vivo with AderbB-2⌬tk induced both protective and therapeutic immunity against tumor cells expressing ErbB-2. 28 In this study, we investigated the antitumor effects of direct intratumoral administration of a recombinant adenovirus vector expressing a kinase dead form of ErbB-2 (AderbB-2⌬tk).…”
Section: ⌬Tk As a Potential Therapeutic Agent For Breast Cancer Usimentioning
confidence: 99%
“…The vaccinia virus is capable of co-presentation of antigen, and constructed vaccinia viruses have been shown to protect animals against infectious disease and tumour challenges (Bennick et al, 1984;Moss et al, 1984;Bernards et al, 1987;Lathe et al, 1987;Moss and Flexner, 1987;Estin et al, 1988). It has been shown that vaccinia virus vectors are stable and that inserted gene products from human colon cancer cell libraries are expressed and normally post-translationally modified (Coupar et al, 1988).…”
Section: Humoral and Cell-mediated Responses To Ceamentioning
confidence: 99%